PENGARUH KOMPETENSI, MOTIVASI KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI (Studi Pegawai Kelurahan di Kecamatan Mijen Kabupaten Demak) - Intan Mayasari, 13.05.51.0031; Rijanti, Tristiana (Students Journal of Economic and Management, 2018)
The purpose of this study was to examine the influence of competence, motivation and compensation on performance (Employee Study in Mijen sub District Demak). The sampling technique used saturated samples / census, where all members of the population were sampled. The sample of the study was 100 respondents. Technique data analysis using validity test, reliability and multiple regression. While the hypothesis test tool using t test. The results showed that competence, motivation and compensation have positive and significant effect on performance. Keywords: Competence, motivation, compensation and performance